2017
DOI: 10.1080/19440049.2017.1301682
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an SPME-GC method for a degradation kinetics study of propiconazole I, propiconazole II and tebuconazole in blueberries in Concordia, the main production area of Argentina

Abstract: An analytical method for the simultaneous determination of propiconazole isomers and tebuconazole residues in blueberries was developed using solid-phase microextraction (SPME) coupled to gas chromatography. Confirmation was performed by gas chromatography-mass spectrometry in selected-ion monitoring mode. The SPME fibre coating selected was CWX-DVB, and the pH was adjusted to 7 with NaOH. The method is selective with adequate precision and high accuracy and sensitivity. Recoveries ranged between 97.4% and 98.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, after the sampling interval (i.e., 21-14 days after treatment), >95% of PCZ residue had degraded in cabbage and spinach while PCZ residue concentration in shallot samples had dissipated by ~90%. These findings agree with those reported in a previous study on PCZ degradation in various fruits, crops, and vegetables [9,12,16,24]. For example, PCZ degraded by >87% in grapes and mangos 3 days post-application and by >97% after 10 days [4].…”
Section: Dissipation Of Propiconazole (Pcz) In Leafy Vegetablessupporting
confidence: 92%
See 1 more Smart Citation
“…However, after the sampling interval (i.e., 21-14 days after treatment), >95% of PCZ residue had degraded in cabbage and spinach while PCZ residue concentration in shallot samples had dissipated by ~90%. These findings agree with those reported in a previous study on PCZ degradation in various fruits, crops, and vegetables [9,12,16,24]. For example, PCZ degraded by >87% in grapes and mangos 3 days post-application and by >97% after 10 days [4].…”
Section: Dissipation Of Propiconazole (Pcz) In Leafy Vegetablessupporting
confidence: 92%
“…A multiregional greenhouse field trial was conducted at three locations, including Gumi-si, (36. 24 [15], each greenhouse was partitioned into plots of 2 m × 15 m in accordance with the preharvest treatment intervals, which corresponded with the fungicide application time and a 1.5 m buffer zone was created between treated plants to avoid cross-contamination. A commercial-grade formulation of PCZ was applied at a dosage of 22 g a.i./ 10 acres employing an electric knapsack sprayer calibrated at 1,500 mL/min.…”
Section: Greenhouse Trial Designmentioning
confidence: 99%
“…It has been reported that PRO was associated with an increase of neurotoxicity, reproductive toxicity and hepatotoxicity accidents . Up to now, most studies on PRO, such as residue, toxicity, dissipation, , or metabolism, were mainly focused on its racemate. Although several studies had reported the bioactivity, acute toxicity, bioaccumulation, biotransformation, and dissipation of PRO in wheat, grapes, and soils at the enantiomeric level, ,, the stereoselective information on PRO enantiomers is still limited and insufficient to comprehensively assess their risks to the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, several analytical methods have been developed to monitor TEB residues in various matrices, such as gas chromatography coupled to nitrogen-phosphorous selective detector (GC-NPD) (Deng, Hu, Qin, & Li, 2010;Singh, Padmaja, & Pandey, 2014), gas chromatography coupled to mass spectrometry (GC-MS) (Dong & Hu, 2014;Liu et al, 2011;Munitz, Medina, & Montti, 2017), as well as high-performance liquid chromatography (HPLC) with ultraviolet detector (Wang et al, 2016;Wu et al, 2014). These analytical assays were sensitive and accuracy, however, their inherent drawbacks lie in sophisticated instruments, highly quality personnels and tedious pretreatment procedure.…”
Section: Introductionmentioning
confidence: 99%